2018
DOI: 10.3399/bjgpopen18x101613
|View full text |Cite
|
Sign up to set email alerts
|

Delivering integrated hypertension care at private health facilities in urban Pakistan: a process evaluation

Abstract: BackgroundIn Pakistan about 18% of all adults are affected by hypertension, and only one in eight of the prevalent cases have their hypertension controlled. As in many other low-middle income countries, a public–private partnership approach is being considered for delivering non-communicable disease care in urban areas.AimThis process evaluation was undertaken to understand how an integrated care intervention was experienced by the care providers and patients, and to inform modifications before possible scalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…8 The intervention was found to have improved the attendance for follow-up visits. However, high attrition (even in intervention arm) does indicate the need for improving treatment adherence through implementation research on various potential options, 18 such as reducing the frequency of follow-up visits (unless clinically indicated), 14 extending the timing of hospital outpatient, adding a treatment supporter, 19 and developing public–private partnership for expanded coverage and continued care. 20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The intervention was found to have improved the attendance for follow-up visits. However, high attrition (even in intervention arm) does indicate the need for improving treatment adherence through implementation research on various potential options, 18 such as reducing the frequency of follow-up visits (unless clinically indicated), 14 extending the timing of hospital outpatient, adding a treatment supporter, 19 and developing public–private partnership for expanded coverage and continued care. 20…”
Section: Discussionmentioning
confidence: 99%
“…About 20% of asthma and COPD patients being prescribed leukotriene modifier tablets seems in line with the generally reported 26 tendency of physicians to overprescribe, even when the drug is not made available for free dispensing. Another study 14 on non-communicable disease care in Pakistan reported the prescription of drugs to be a blend of doctor and patient preferences, with some doctors prescribing high-cost pharmaceutical products because of fancy packaging and active marketing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A process evaluation of the trial, published in this journal, 20 indicated that offering programme-endorsed hypertension care at private clinics, during the first 9 months after registration, was feasible for the clinic staff and acceptable to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…To keep the trial evidence relevant to the real-life programme implementation processes, any special measure for an enhanced staff adherence to the intervention protocol was deliberately avoided. Staff and patient adherence, and challenges to the intervention protocols, have been studied and published in this journal, 20 and the guides and tools are available at .…”
Section: Methodsmentioning
confidence: 99%